Grain boundary and dislocation strengthening of nanocrystalline NiTi for stable elastocaloric cooling. (15th March 2023) - Lin, Hongyang; Hua, Peng; Huang, Kai; Li, Qiao; Sun, Qingping
Abstract: We fabricate a nanocrystalline NiTi with an average grain size of 31 nm and high-density (4.7 × 10 15 m − 2 ) dislocations via cold rolling (38% thickness reduction) and annealing (310 ℃, 2 min) for elastocaloric cooling. It is found that the high-density-dislocation nanocrystalline NiTi shows a high yield strength of 2.09 GPa, a large and stable average temperature drop ( ΔT ) of 17.3 ℃ over 10 6 phase-transition cycles under the stress of 1.4 GPa at room temperature. The high cyclic stability originates from grain boundary and dislocation strengthening mechanisms, where the grain boundaries and the high-density dislocations suppress the nucleation of transformation-induced dislocations. The simple and effective processing route via cold rolling and low-temperature annealing is applicable to mass production of bulk nanostructured NiTi with stable elastocaloric cooling performances. Graphical abstract: Image, graphical abstract